A principle of extended producer’s responsibility in the law of waste management - Korzeniowski, Piotr (Acta Universitatis Lodziensis. Folia Iuridica, 2015)
A principle of extended producer’s responsibility in the law of waste management pursues the following aims of the waste management: 1) the maximum decrease in the amount of waste in any type of business and human existence, 2) the immediate reuse of production waste in a manufacturing process, 3) recovery of raw materials from collected waste, 4) application of processes to dispose of waste, 5) orderly waste storage ensuring the least damage to the environment. The overriding objective of this principle is application of legal instruments encouraging producers to undertake activities which will: prevent production of waste, decrease the level of using materials and energy at every stage of a product life cycle and encourage to introduce changes in the phase of a product design and during its manufacture. Broadly speaking, a principle of extended producer’s responsibility is connected with a producer’s financial liability for a product. In a legal structure of the extended producer’s responsibility we deal with preventive liability. This principle completes a principle of incurring costs of waste management.